Telepharmacy during home isolation: drug-related problems and pharmaceutical care in COVID-19 patients receiving antiviral therapy in Thailand - Worapong Sungsana; Chotirat Nakaranurack; Benjabhorn Weeraphon; Watsa Charoenwaiyachet; Supparat Chanprasert; Pattama Torvorapanit; Wichai Santimaleeworagun; Opass Putcharoen (Taylor & Francis Group, 2023)
Abstract Background Home isolation has been proposed for coronavirus disease 2019 (COVID-19) patients with mild symptoms to avoid hospital overcrowding. This study aimed to describe the drug-related problems (DRPs) and the pharmaceutical care of home-isolating COVID-19 patients in Thailand. Methods Our cross-sectional study was undertaken from July 1 to September 30, 2021, at the King Chulalongkorn Memorial Hospital, Thailand. Patients who were ≥ 18 years old, were diagnosed with mild COVID-19 by real-time polymerase chain reaction (RT-PCR), and were able to isolate at home while receiving an antiviral agent and standard symptomatic treatment were enrolled. Infectious disease pharmacists provided a telepharmacy service on days 1 and 3 after the COVID-19 diagnosis. Results A total of 197 patients met the study criteria. Their median age was 45 years, and their most common underlying disease was hypertension (44.29%). All patients exhibited excellent anti-COVID-19 drug adherence. We identified 125 DRPs, including adverse reactions (68%), and the unnecessary use of products (62.40%). Moreover, 91 patients (46.19%) reported the use of supplements or herbs, with vitamin C being the main supplement (37.36%). Pharmacists provided 36 recommendations and received 33 questions from COVID-19 patients. Conclusions Our study demonstrates that telepharmacy is an essential service for detecting and preventing DRPs in home-isolating COVID-19 patients.